2016
DOI: 10.1097/aud.0000000000000205
|View full text |Cite
|
Sign up to set email alerts
|

Finite Verb Morphology in the Spontaneous Speech of Dutch-Speaking Children With Hearing Loss

Abstract: When producing finite verb morphology, profoundly deaf children wearing CIs perform similarly to their peers with moderate-to-severe hearing loss wearing HAs. Hearing loss negatively affects the acquisition of subject-verb agreement regardless of the hearing device (CI or HA) that the child is wearing. The results are of importance for speech-language pathologists who are working with children with a hearing impairment indicating the need to focus on subject-verb agreement in speech-language therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…On the other hand, experimental probes have tended to identify persistent delays and/or deficits in both the perception and production of grammatical morphemes and syntax (Brown, 1984;Delage & Tuller, 2007;DesJardin, Ambrose, Martinez, & Eisenberg, 2009;Hammer & Coene, 2016;Koehlinger, Van Horne, & Moeller, 2013;McGuckian & Henry, 2007;Moeller et al, 2010;Norbury et al, 2001;Tomblin et al, 2015), including reductions in mean length of utterance (Koehlinger et al, 2013). For instance, such studies have shown that children and/or adolescents with MMHL show delays and/or deviancies in their production of English, French, and Dutch grammatical morphemes (Brown, 1984;Delage & Tuller, 2007;Hammer & Coene, 2016;McGuckian & Henry, 2007;Moeller et al, 2010;Norbury et al, 2001;Tomblin et al, 2015). Moreover, the limited numbers of studies that have examined syntactic development in children with mild to severe SNHL have tended to identify patterns of impaired performance even into adolescence (Delage & Tuller, 2007;Elfenbein, Hardin-Jones, & Davis, 1994;Moeller et al, 2010;Tuller & Delage, 2014;Tuller & Jakubowicz, 2004;cf.…”
mentioning
confidence: 99%
“…On the other hand, experimental probes have tended to identify persistent delays and/or deficits in both the perception and production of grammatical morphemes and syntax (Brown, 1984;Delage & Tuller, 2007;DesJardin, Ambrose, Martinez, & Eisenberg, 2009;Hammer & Coene, 2016;Koehlinger, Van Horne, & Moeller, 2013;McGuckian & Henry, 2007;Moeller et al, 2010;Norbury et al, 2001;Tomblin et al, 2015), including reductions in mean length of utterance (Koehlinger et al, 2013). For instance, such studies have shown that children and/or adolescents with MMHL show delays and/or deviancies in their production of English, French, and Dutch grammatical morphemes (Brown, 1984;Delage & Tuller, 2007;Hammer & Coene, 2016;McGuckian & Henry, 2007;Moeller et al, 2010;Norbury et al, 2001;Tomblin et al, 2015). Moreover, the limited numbers of studies that have examined syntactic development in children with mild to severe SNHL have tended to identify patterns of impaired performance even into adolescence (Delage & Tuller, 2007;Elfenbein, Hardin-Jones, & Davis, 1994;Moeller et al, 2010;Tuller & Delage, 2014;Tuller & Jakubowicz, 2004;cf.…”
mentioning
confidence: 99%
“…However, the overall picture is far from clear. Some studies indicate no difference in language outcomes in children with HAs compared to children with CIs (Fitzpatrick, Crawford, Ni, & Durieux-Smith, 2011;Hammer & Coene, 2016). Others studies find similar or better language outcomes in children with HAs compared to children with CIs (Fitzpatrick et al, 2012), while still others find CI use to be predictive of better language outcomes in children with hearing loss compared HA use (Sininger et al, 2010).…”
Section: Language Outcomes In Children With Hearing Lossmentioning
confidence: 99%
“…The morphological development of children with CIs deviates from children with NH, as it is strongly influenced by the perceptual prominence of the morphological forms (e.g., aquisition of perceptually more salient copula-"is" and "are"-before acquisition of noun plurals in English [Svirsky, Stallings, Lento, Ying, & Leonard, 2002] and the acquisition of inflectional morphology on nouns and verbs before acquisition of unstressed articles in German [Szagun, 2000]). Children with CIs make more inflectional errors on finite verbs than children with NH in their spontaneous speech (Hammer & Coene, 2016). Also their syntactic development deviates from children with NH.…”
Section: Morphosyntactic Development In Children With Cismentioning
confidence: 86%